Sistema kontrolya psikhofizicheskogo sostoyaniya cheloveka kak instrument uprableniya protsessom adaptatsii v sporte i uchebnom protsesse - Zhbankov, O. V.; Petrov, D. S.; Golovina, V. A. (Teorija i Praktika fiziceskoj Kul'tury, 2003)
The adaptive changes of the functional condition of various systems of the organism of the athlete under the influence of training and competitive loads occurs heterochronically. The reaction of various systems at different stages of this process is the specific and not always possible for operative diagnostics. The important point in an estimation of the functional condition of the person-operator (conditions of activity of the athlete in the general view corresponding to the definition "person-operator") is the level of the neuropsychical pressure. There are known two types of unbalasing of regulative function in this area - the hypermobilization and the development of braking processes. Both of them can be defined as the polar displays of psychophysical conditions (PPC). On the basis of the analysis of characteristics of the devices the authors used for the measurement of PPC the method of Fere, as the steadiest to embarrassments of variable type. After that the hardware-software complex "Visual SGR" for testing of PPC was developed.